Effectiveness of Using Analog Grid and Virtual Grid in Thoracic Radiography Examination - Mahanani, Ayu; Anshor Nugroho; Arnefia Mei Yusnida (Jurusan Teknik Elektromedik, Politeknik Kesehatan Kemenkes Surabaya, Indonesia, 2025)
Chest radiography is essential for diagnosing thoracic abnormalities, but scattered radiation often reduces image contrast and diagnostic accuracy. Conventional analog grids mitigate scatter yet increase patient dose, while virtual grids offer digital correction with potentially lower radiation exposure. This study aimed to compare image quality and radiation efficiency between analog and virtual grids in thoracic radiography, contributing empirical evidence on the feasibility of adopting virtual grids as safer and more efficient alternatives. Three imaging protocols (Analog Grid, Virtual Grid 1, and Virtual Grid 2) were compared using identical exposure parameters on a phantom. Image quality was evaluated both objectively and subjectively. Results showed that Virtual Grid 2 achieved the highest score (4.47), slightly outperforming the Analog Grid (4.20) despite using lower radiation, while Virtual Grid 1 scored the lowest. ANOVA confirmed significant differences among the three methods, though the t-test between Analog Grid and Virtual Grid 2 showed no significant difference. A moderate negative correlation indicated that a reduced dose does not always compromise image quality when supported by advanced processing. In conclusion, Virtual Grid 2 demonstrates strong potential as a reliable alternative to analog grids, enabling excellent image quality with minimal radiation and supporting safer radiographic practices.